(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information on the development of critical thinking skills on the basis of the cluster method in interactive study of the topic “internal waters and water resources of Uzbekistan” in the course of “Natural geography of Uzbekistan”, talks about the advantages of the cluster method in quick and easy study of sources in the text of the textbook in geography education. Information about the application of the cluster method in the study of the course of “ Natural geography of Uzbekistan” is given.